2009
DOI: 10.1248/bpb.32.427
|View full text |Cite
|
Sign up to set email alerts
|

Fibroin-Derived Peptides Stimulate Glucose Transport in Normal and Insulin-Resistant 3T3-L1 Adipocytes

Abstract: Fibroin, the protein of silk, and hydrolyzed fibroin have recently been described to enhance insulin sensitivity and glucose metabolism in 3T3-L1 adipocytes. Here, we report that a series of synthetic peptides derived from the fibroin sequence have enhancing effects on glucose transport in normal and insulin-resistant 3T3-L1 cells. We observed that, among several enzymatic hydrolysates of fibroin, the chymotryptic and peptic hydrolysates were significantly more effective than others in augmenting insulin-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…14 Besides, fibroin is not only an inert drug carrier. The peptides resulting from its hydrolysis have shown therapeutic potential, for instance, in the stimulation of glucose transport in normal and insulin-resistant 3T3-L1 adipocytes 15 or in the proliferation of fibroblasts in wound healing models. 11 Kim et al also reported the anti-inflammatory activity of fibroin peptides in a mice edema model of inflammation.…”
mentioning
confidence: 99%
“…14 Besides, fibroin is not only an inert drug carrier. The peptides resulting from its hydrolysis have shown therapeutic potential, for instance, in the stimulation of glucose transport in normal and insulin-resistant 3T3-L1 adipocytes 15 or in the proliferation of fibroblasts in wound healing models. 11 Kim et al also reported the anti-inflammatory activity of fibroin peptides in a mice edema model of inflammation.…”
mentioning
confidence: 99%
“…The reason may be the capability of SF to motivate several cell signaling pathways leading to improved secretion of collagen matrix compared to PLACL scaffolds. 43 Generally, PLACL biopolymers support the cell growth by adding VE; Cur induce the secretion of ECM in fibroblast cells. The results …”
Section: Secretion Of Collagenmentioning
confidence: 99%
“…Hydrolysates of silk fibroin (HSF) are water-soluble peptides that have been investigated as food and dietary supplements. HSF contains 18 different amino acids, including Gly (45.9%), Ala (30.3%), Ser (12.1%), Tyr (5.3%), and Val (1.8%) (Kim et al, 2009;Tsukada et al, 1994). Numerous studies have documented a range of effects of HSF, including moisturizing effects (Nishida et al, 2010), wrinkle reduction, inhibition of tyrosinase (Kato et al, 1998), and apoptosis (Acharya et al, 2008).…”
Section: Cell Population Growth Assaymentioning
confidence: 99%